Formação do profissional de saúde no atendimento do paciente surdo: uma análise da inserção da LIBRAS nos Cursos de Graduação em Medicina e em Odontologia da UFMA - FERREIRA, Clayton Gabriel Pavão (2023)
The diversity of patients who look for health services in different areas, something which makes communication crucial for effective service, stems from the communication between medical and/or dental professionals and their patients. As such, it is possible to include deaf people who communicate in Brazilian sign language (LIBRAS), which although legally recognized in Brazil, is not very widespread or known. This study has been derived from exploratory and descriptive research with a qualitative approach and was developed at the Federal University of Maranhão in the undergraduate medicine and odontology courses. Therefore, the main problem of this study is: How has including Brazilian sign language in the medicine and odontology courses at UFMA and the initial training of future health professionals in relation to communication for deaf students been coming along? And the specific objectives are: Mapping students and teachers from the medicine and odontology courses at UFMA; verify if the undergraduate health courses at UFMA contain a Brazilian sign language class and if it has been operationalized in the medicine and odontology courses. Know the curricular structure of the odontology and medicine courses, the theoretical and methodological aspects that instrumentalize future professionals in the areas listed in the care of deaf people; identify the communication strategies that current and future professionals in the investigated areas use to establish interaction with deaf patients; describe the extent to which UFMA works on specific issues, with the purpose of preparing Medical and odontology students to care for deaf patients. There were eighteen participants including academics and professors from the odontology and Medicine courses at the Federal University of Maranhão UFMA. Data was collected through semi-structured interviews. Research findings revealed that although the HEI surveyed has been making efforts to promote accessibility, it has not been adequately preparing future professionals in the areas mentioned so that they can assist deaf or hearing-impaired patients, which is due to the early stages of the Brazilian sign language class where the research took place and that reflect this same scenario in other classes.